2017
DOI: 10.18632/oncotarget.19879
|View full text |Cite
|
Sign up to set email alerts
|

Chronic high dose of captopril induces depressive-like behaviors in mice: possible mechanism of regulatory T cell in depression

Abstract: Major depression has various types of symptoms and disease courses with inconsistent response to monoamine-related antidepressants. Thus, monoamine theory may not be the only pathophysiologic pathway relevant to depression. Recently, it has been suggested that regulatory T cell (Treg) is associated with depression. Based on our previous study that showed decreased regulatory T cell (Treg) population following chronic high-dose captopril (CHC, 40 mg/kg/day * 21 days) administration, we examined whether CHC alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
(84 reference statements)
2
16
0
Order By: Relevance
“…Furthermore, the present study demonstrated that SGK1 inhibitor EMD638683 significantly inhibited the increased peripheral cytokines in AngII-induced hypertensive mice. This finding is consistent with previous studies showing that peripheral cytokines such as IL-17, IL-6, IL-1β, Interferonγ (IFN-γ), monocyte chemoattractant protein 1 (MCP-1), vascular endothelial growth factor (VEGF), and TNF-α were increased and contributed to target organ damages in AngII-induced hypertension in mice ( Lee et al, 2006 ; Sanchez-Lemus et al, 2009 ; Madhur et al, 2010 ; Mirhafez et al, 2014 ; Park et al, 2017 ). For example, it has been shown that IL-17 production from T cells and IL-17 protein in the aortic media, and that the IL-17 deficiency displayed preserved vascular function, decreased superoxide production, and reduced T-cell infiltration in response to angiotensin II ( Madhur et al, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the present study demonstrated that SGK1 inhibitor EMD638683 significantly inhibited the increased peripheral cytokines in AngII-induced hypertensive mice. This finding is consistent with previous studies showing that peripheral cytokines such as IL-17, IL-6, IL-1β, Interferonγ (IFN-γ), monocyte chemoattractant protein 1 (MCP-1), vascular endothelial growth factor (VEGF), and TNF-α were increased and contributed to target organ damages in AngII-induced hypertension in mice ( Lee et al, 2006 ; Sanchez-Lemus et al, 2009 ; Madhur et al, 2010 ; Mirhafez et al, 2014 ; Park et al, 2017 ). For example, it has been shown that IL-17 production from T cells and IL-17 protein in the aortic media, and that the IL-17 deficiency displayed preserved vascular function, decreased superoxide production, and reduced T-cell infiltration in response to angiotensin II ( Madhur et al, 2010 ).…”
Section: Discussionsupporting
confidence: 93%
“…Behavioral testing. Behavior testing was performed according to our previous studies 26 www.nature.com/scientificreports/ www.nature.com/scientificreports/ Figure 7. Schematic representation of ANGII-induced depressive-like behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…However, a recent study reported that chronic high-dose captopril (CHC) administration can induce a specific form of depressive-like behavior. This effect is caused by Treg reduction and microglial activation with unaltered CRF levels and HPA axis activity (Park et al, 2017). This finding suggests that the activation of immune cells as a response to depression can also be independent of CRF and the HPA axis regulation.…”
Section: Crf Cytokines and Immune Cells In Depressionmentioning
confidence: 99%